2014
DOI: 10.1080/01441647.2014.975169
|View full text |Cite
|
Sign up to set email alerts
|

Train delay and perceived-wait time: passengers' perspective

Abstract: Waiting time influences the overall perception of service quality. The passengerperceived waiting time can determine their waiting experience. The concept of waiting time refers to the comparison between the passengers' inherent tolerance of waiting and the possible improvement scenarios. This study investigates the passengers' tolerance of waiting under various scenarios of train delays in order to improve their perceived waiting time. We propose the adoption of a modern psychometric method utilizing the Rasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 82 publications
1
10
1
Order By: Relevance
“…Consumer sustainability preferences (Attari, DeKay, Davidson, & Bruin, 2010;Daziano & Chiew, 2012;Feng, Fullerton, & Gan, 2013;Gould & Golob, 1997;Li, Clark, Jensen, Yen, & English, 2013;Marigny Research Group, 2006;Sheth, Sethia, & Srinivas, 2011 (Jacobsen & van Benthem, 2013;Marell, Davidsson, & Gärling, 1995) Public transit  Influence of gas price on transit ridership (Lane, 2010(Lane, , 2012 Passenger perspective on train delay (Cheng & Tsai, 2014)…”
Section: Appendix a Answering Questions About Pev Consumersmentioning
confidence: 99%
“…Consumer sustainability preferences (Attari, DeKay, Davidson, & Bruin, 2010;Daziano & Chiew, 2012;Feng, Fullerton, & Gan, 2013;Gould & Golob, 1997;Li, Clark, Jensen, Yen, & English, 2013;Marigny Research Group, 2006;Sheth, Sethia, & Srinivas, 2011 (Jacobsen & van Benthem, 2013;Marell, Davidsson, & Gärling, 1995) Public transit  Influence of gas price on transit ridership (Lane, 2010(Lane, , 2012 Passenger perspective on train delay (Cheng & Tsai, 2014)…”
Section: Appendix a Answering Questions About Pev Consumersmentioning
confidence: 99%
“…Carrion [8] provided a case analysis for this error using self-reported as well as GPS measured travel times and suggested that perception error regarding travel time can influence travel behavior. Cheng and Tsai [9] studied travelers' perceptions of travel time through a questionnaire survey. They found that travel time perceptions can be influenced by personal characteristics such as gender and age.…”
Section: Introductionmentioning
confidence: 99%
“…These disruptions generate delays in trains schedule and also affect the timetable of the other trains. In this paper, the train reliability criterion is calculated using Equation (2). It calculates the percentage of trains arrived at destination within the allowable delay range:…”
Section: Reliability Assessmentmentioning
confidence: 99%
“…Train delays depend on the traffic volume and the capacity utilization and comprise a significant percentage of the travel time. Furthermore, the delays cause high costs of passenger dissatisfaction and penalties for late deliveries of freight for railway companies [2]. In this situation, the management of train services is a complex procedure [3].…”
Section: Introductionmentioning
confidence: 99%